Articuler l’expérience et le discours : réflexions à partir du poststructuralisme et de la phénoménologie féministe - Mickaëlle Provost (Glad!, 2021)
This article raises the issue of the relationship between lived experience and language, by bringing into dialogue two seemingly incompatible positions within feminist philosophy: one poststructuralist, the other phenomenological. First, I analyze the poststructuralist position according to which experience is constituted by a set of discursive norms. In a second step, I study the phenomenological criticism addressed to this position, by underlining the singularity and the complexity of the concept of experience: experience can include some unspeakable or inexpressible dimensions, without being entirely irreducible to social and discursive conditions. For this reason, it seems useful to explore the conceptual distinction between "discourses" and "language". Finally, I consider Simone de Beauvoir’s Second Sex as an illuminating perspective on the relationship between experience and discursive norms, managing to articulate a phenomenological approach and an analysis of the discursive formation of lived experience.